simply The following
Attachments:
![](https://hi-static.z-dn.net/files/d36/aca3dbd4a0769638ac17ef97603045a1.jpg)
Answers
Answered by
0
Answer:
your answer is given above.
Attachments:
![](https://hi-static.z-dn.net/files/dfa/fadfb7842e8cfa18d9824193998fe4e5.jpg)
Answered by
0
Answer:
(a²+b²)(a²+b²) - (a²-b²)(a²-b²)
= (a²+b²)²-(a²-b²)²
= (a²+b²-a²+b²)(a²+b²+a²-b²)
= 2b²× 2a²
= 4a²b²
Step-by-step explanation:
Similar questions
Math,
5 months ago
Social Sciences,
5 months ago
Math,
5 months ago
Social Sciences,
11 months ago
English,
11 months ago